Ægteskabet mellem Himmel og Helvede - Petersen, Hans Alstrup (Religionsvidenskabeligt Tidsskrift, 1988)
Inspired by Georges Bataille’s heterology and Roland Barthes’ sequential reading-procedure this article presents a close reading of The Ring, the last story in Karen Blixen’s/Isak Dinesen’s Anecdotes of Destiny (1958). Following the story step by step especial interest is shown to its topography: the paradigmatic articulation of a cryptic, sacred place – which is also the woman’s place – where the fundamental heterogeneity of the text is figured in a passionate pantomime. The article emphasizes the intimate relationship between literature and religion – and the way the text communicates not primarily a meaning or a message, but more fundamentally – with the reader’s passion.